Beyond conventional aqueous electrolytes: Recent developments in Li‐free “water‐in‐salt” electrolytes for supercapacitors - Kim, Jongyoon; Lee, Subin; Lee, Dongwook; Yoo, Seung Joon (Bulletin of the Korean Chemical Society, 2023)
Water‐in‐salt electrolyte (WiSE) is an extremely high‐concentration aqueous solution where the salt outnumbers the solvent by weight and/or volume. Supercapacitors (SCs) incorporating lithium‐free WiSE are promising energy storage systems due to their wide electrochemical stability window (ESW), high‐ionic conductivity, low cost, and ecofriendliness. This review provides an overview of WiSE‐based SCs, focusing on physicochemical properties, recent progress, and prospects of non‐lithium WiSE‐based SCs. The mechanisms of how WiSEs exhibit expanded ESW, high‐ionic conductivity, and low‐temperature tolerance are elaborated. Then, we summarized the current strategies for the lithium‐free WiSE‐based SCs categorized by cations (Na+, K+, other metallic cations, and non‐metallic cations). In addition, the utilization of redox additives in WiSE‐based SCs is presented. Finally, current challenges and perspectives for the application of Li‐free WiSE into SCs are provided. The “Water‐in‐salt” electrolyte (WiSE) is a promising class of electrolyte because of its unique physicochemical properties. This review highlights the recent progress of WiSE and its application to supercapacitors (SCs). Our discussion is primarily focued on operatig mechanisms of non‐Lithium based WiSE and how they affect performance. Current challenges and perspectives are also discussed.